Elementary decomposition of soliton automata - Bartha, Miklós; Krész, Miklós (Acta Cybernetica, 2000)
Soliton automata are the mathematical models of certain possible molecular switching devices. In this paper we work out a decomposition of soliton automata through the structure of their underlying graphs. These results lead to the original aim, to give a characterization of soliton automata in general case.